The mediating role of emotional intelligence and emotional resistance between interpersonal mindfulness and teacher- student interaction among teachers in China - Jiayuan, Ma; Hidayat, Riyan (Springer, 2025)
Success in school depends on effective teacher-student relationships, and educational methods can be greatly improved by knowing the variables that affect these interactions. The purpose of this study was to determine how emotional resistance and emotional intelligence, among English teachers in China, mediate the relationship between interpersonal mindfulness and teacher-student interactions. The sample for this quantitative study consisted of 200 English teachers from different parts of China. The suggested model was thoroughly examined using AMOS version 18.0 and structural equation modeling (SEM). The initial measurement models for emotional intelligence, emotional resistance, interpersonal mindfulness and teacher-student interaction demonstrated acceptable fit with the data, as determined through maximum likelihood estimation. The findings revealed that interpersonal mindfulness positively influences teacher- student interactions, with emotional intelligence and emotional resistance serving as significant partial mediators. These findings provide educators and policymakers with insightful information, indicating that improving teachers’ emotional intelligence and mindfulness can improve student outcomes. This study emphasizes the significance of psychological characteristics in educational environments, adding to the theoretical and practical expertise in the subject.